SISTEM PAKAR DIAGNOSA PENYAKIT GINJAL DAN SALURAN KEMIH DENGAN METODE BREADTH FIRST SEARCH - Yogi Aditya Pratama; Erfian Junianto (Jurnal Informatika, 2016)
Abstract - Currently kidney disease affects adult mortality throughout the world especially continent of Asia, Australia, Northern Europe, and South America. Kidney disease can be a strong indicator of risk of death and end-stage renal disease. The cause of kidney disease is affecting due to lack of knowledge about the information the symptoms that arise in kidney disease and also the lack of health services and facilities especially to the kidney disease itself. An expert system is a knowledge-based system program that provides a solution that can solve the problem as it is usually done by experts. Development of an expert system using Breadth First Search method, which has advantages such as not going to hit a dead end in the search process solution, if there is more than one solution, the minimum solution will be selected to perform diagnosis of kidney and urinary tract diseases. So with this expected applications can improve the performance of health services and facilities, as well as the patient can take further action without having to wait for a doctor's examination.